Analisis Hukum Zakat Menurut UU.38 Tahun 1999 dalam Perspektif Hukum Islam - Mohammad Ridwan (LPPM STAIS Dharma Indramayu, 2020)
This study has the aim to be formulated, namely knowing: 1) Analysis of Law No. 38 of 1999 in terms of management, and utilization of zakat; 2) Relevance of Law Number 38 of 1999 on the management of zakat. The research method uses descriptive qualitative by collecting data using observation, library research, and documentation. Based on the results of the study it can be concluded that 1) Analysis of zakat based on the Act. No. 38 of 1999 explained that the management of zakat is the activity of planning, organizing, implementing, and controlling the collection and distribution and utilization of zakat, 2) The relevance of zakat law in the law no.38 of 1999 concerning zakat has links with Islamic law, especially related to Islamic law with amyl. The relationship between amil and zakat that has been legislated has many connections, namely the formation of amil zakat institutions formed by the local government as zakat houses.